Acritarchs of the Ediacaran Frecheirinha Formation, Ubajara Group, Northeastern Brazil - Chiglino,Leticia (2015)
We report for the first time the occurrence of organic-walled microfossils in Ediacaran limestones and marls of the Frecheirinha Formation, Ubajara Group, and the first Precambrian acritarchs so far reported for northeastern Brazil. The assemblage of the Frecheirinha Formation represents a low-diversity microflora comprising Leiosphaeridia, Lophosphaeridium and subordinated Bavlinella (=Sphaerocongregus). Their thermal alteration index (TAI) between 4+ and 5, suggests metamorphic temperatures exceeding 200-250°C. Higher temperatures are probably related to intruding granitic plutons (Meruoca, Mucambo). Reported δ13C values of carbonates of -3.5 ‰ VPDB (Vienna-Peedee Belemnite) at the base, passing up section into a positive plateau of up to +3.7 ‰, and corresponding 87Sr/86Sr values between 0.7075 and 0.7080 suggest an Ediacaran age. The acritarch assemblage is comparable to the Late Ediacaran Leiosphere Palynoflora (LELP) or Kotlin-Rovno assemblage, in broad agreement with chemostratigraphic data. Macrofossils belonging to the Ediacara fauna were reported from the overlying Jaibaras Group, which would constrain even further the depositional age of the Frecheirinha Formation to within ca. 575-555 Ma. A more comprehensive palynological study of the Frecheirinha Formation is necessary to confirm this age assignment.